2014
DOI: 10.1002/dmrr.2599
|View full text |Cite
|
Sign up to set email alerts
|

Circulating SFRP5 levels are elevated in drug‐naïve recently diagnosed type 2 diabetic patients as compared with prediabetic subjects and controls

Abstract: Circulating SFRP5 levels were independently associated with T2D as compared with prediabetes and normal glucose tolerance state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 27 publications
4
25
1
Order By: Relevance
“…The use of dynamic measures of beta-cell function after ingestion of glucose in the OGTT might explain that we found an inverse association between circulating Sfrp5 and beta-cell function, whereas two human studies using HOMA-B as marker of fasting beta-cell function failed to find any significant association between these parameters (r = 0Á14 to À0Á05, P > 0Á05) [21,22]. This inverse correlation may appear surprising given that individuals with IGT/T2D had both reduced Sfrp5 levels and decreased C-peptide-derived beta-cell function compared to individuals with NGT.…”
Section: The Inverse Relationship Between Serum Sfrp5 and Beta-cell Fmentioning
confidence: 69%
See 1 more Smart Citation
“…The use of dynamic measures of beta-cell function after ingestion of glucose in the OGTT might explain that we found an inverse association between circulating Sfrp5 and beta-cell function, whereas two human studies using HOMA-B as marker of fasting beta-cell function failed to find any significant association between these parameters (r = 0Á14 to À0Á05, P > 0Á05) [21,22]. This inverse correlation may appear surprising given that individuals with IGT/T2D had both reduced Sfrp5 levels and decreased C-peptide-derived beta-cell function compared to individuals with NGT.…”
Section: The Inverse Relationship Between Serum Sfrp5 and Beta-cell Fmentioning
confidence: 69%
“…Another study found that Sfrp5 overexpression in mice increased the ratio proinsulin/C-peptide which suggests an unfavourable role in the normal insulin maturation process [25]. Two studies in humans failed to observe any association between serum Sfrp5 and homoeostasis model assessment of beta-cell function (HOMA-B), a surrogate marker of beta-cell function [21,22], but data based on dynamic (e.g. oral glucose tolerance test (OGTT)-based) measures of insulin secretion and beta-cell function are currently lacking.…”
Section: Original Articlementioning
confidence: 99%
“…Additionally, two studies also reported lower Sfrp5 levels in patients with type 2 diabetes compared to individuals with normal glucose tolerance [11, 12]. However, it is in contrast to two human studies which found a positive [10] and no relationship [14] to HOMA-IR or higher Sfrp5 levels in patients with type 2 diabetes compared to prediabetic individuals, although no difference to the group with normal glucose tolerance was observed [14]. Different laboratory methods cannot explain the observed differences because this study and the aforementioned studies [1015] used the same method to measure circulating SFRP5 (purchased from Cloud-Clone, previously distributed by USCN).…”
Section: Discussionmentioning
confidence: 98%
“…However, the previous studies were based on small sample sizes, they were not population-based and differed in their adjustment for potential confounders. In particular the study with the opposing result of higher Sfrp5 levels in patients with type 2 diabetes was based on highly selected individuals with optimal glycaemic control (median HbA1c 5.8%) who cannot be considered representative for people with type 2 diabetes in the general population [14]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation